Colorimetric detection of streptomycin in milk based on peroxidase-mimicking catalytic activity of gold nanoparticles. Issue 61 (7th August 2017) - Zhao, Jing; Wu, Yuangen; Tao, Han; Chen, Huayun; Yang, Wenping; Qiu, Shuyi
Abstract : A novel and effective colorimetric aptasensor based on enhanced peroxidase-mimicking catalytic ability of AuNPs was proposed for streptomycin detection. Abstract : A novel colorimetric aptamer sensor (aptasensor) for the detection of streptomycin (STR) is developed based on the peroxidase-like activity of gold nanoparticles (AuNPs) and their interaction with STR-aptamer complex. It is known that AuNPs can easily oxidize substrates in the presence of hydrogen peroxide in a manner identical to peroxidase and 2, 2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) is a commonly used peroxidase substrate with green oxidation product and a characteristic absorption peak at 733 nm. In the absence of STR, STR1 aptamer is adsorbed on the surface of AuNPs, and restrains its catalytic activity due to shield effect of ssDNA sequence against substrates. STR first binds with STR1 aptamer to form an STR-aptamer complex; thus, aptamer sequences do not get absorbed on the surface of the nanoparticles and their peroxidase activity is further greatly enhanced by the STR-aptamer complex, which enables AuNPs to catalyse the oxidation of the substrates. To achieve a higher level of sensitivity, several key parameters of the proposed aptasensor such as pH, concentrations of STR1 aptamer and AuNPs, and incubation and reaction temperature have been investigated. Under optimal conditions, the proposed aptasensor can detect STR in a linear range from 0.1 μM to 0.5 μM with a limit of detection (LOD) as low as 86 nM and exhibits good selectivity. Moreover, further studies also validate the applicability of the proposed aptasensor in milk samples, revealing that it may have enormous potential utility for practical STR detection in food products in the future.